A Systematic Method for Identification of Anti-patterns in Service Oriented System Development - Mohammad Ali Torkamani; Hamid Bagheri (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Service-Oriented Architecture is one of the popular software architecture's patterns used for developing lots of modern systems. However, it has been involved in many failures. Anti-patterns are solutions which have good view, but in fact they are wrong solutions that cause failure of systems. There are a lot of anti-patterns for SOA and new anti-patterns are revealed every day. Anti-patterns have their own reasons for being formed and also they are appeared in special area of the problem. As human's mind is restricted and it can process a limited number of states (piece of information) therefore identification of anti-patterns will be difficult for architects. In this paper, we propose a systematic method based on repository of anti-patterns along with a check list to identify anti-patterns of SOA. This method will assist architects to easily detect and avoid anti-patterns in development process and so escape from risks which related to anti-patterns. Furthermore, in this paper, we present a repository of forty five general anti-patterns in SOA. Reviewing these anti-patterns will help developers to work with clear understanding of patterns in phases of software development and so avoid from many potential problems. Also, our method is evaluated in action.DOI:http://dx.doi.org/10.11591/ijece.v4i1.4097